Amide Synthesis from Esters with Nitriles under Solvent-free Conditions Using Molecular Iodine as a Catalyst (Journal of Oleo Science, 2012)
The reaction of esters with nitriles, using iodine as a catalyst under solvent-free conditions, was investigated. For example, 1-phenylethyl acetate reacted with benzonitrile in the presence of iodine to afford the amide, N-(1-phenylethyl)benzamide. Addition of water was effective in promoting amidation. The most suitable conditions were investigated, and determined as follows: temperature = 80°C, molar ratio of nitrile:alcohol:iodine:water = 1:3:0.2:1.0, and reaction time = 18 h. The amidation reactivity depended on the stability of the cationic intermediate formed from the ester. Only the reaction of 2-phenylpropan-2-yl acetate with benzonitrile gave no amide compound; rather, the cyclic compound, 1,1,3-trimethyl-3-phenyl-2,3-dihydro-1H-indene was obtained in 90% yield. The reaction of (-)-bornyl acetate with benzonitrile produced the racemic amide compound, (±)-exo-N-isobornylbenzamide, in 82% yield.